Identità e medicina narrativa: una prospettiva filosofica - Lovecchio, Chiara (B@belonline, 2020)
Illness changes the sense of personal identity. Illness opens the philosophical reflection on the narrative perspective: I would like to see how Paul Ricoeur’s reflections can be linked to the narrative medicine field. The concept of narrative identity can be seen as a foundation for the narrative medicine that aims to put the patient at the centre of the healing processes, with his/her social, emotional and relational context.